A new species of Holcoglossum (Orchidaceae, Aeridinae) from Southern Shan State, Myanmar with taxonomic notes on Holcoglossum himalaicum - Wojtas, K. Philip; Bandara, Champika; Kumar, Pankaj (Phytotaxa, 2024)
A new species of Holcoglossum is described and illustrated from Myanmar with colour plates, line drawing and photographs. The comparison and differentiation are made with H. semiteretifolium and H. himalaicum. Holcoglossum clausum is allied to H. himalaicum owing to the similar coloration and the long spur, however, they differ based on the size of the petals (7–8 mm × 2–3 mm vs. 4–5 mm × 2 mm), the length of the petiole (1.8 cm vs. 3–4 cm) and the length of the stem (4 cm vs. 5–24 cm). From H. semiteretifolium the new species can be distinguished by its growth (pendant vs. upright), the much longer leaves (45 cm vs. 15 cm) and the longer spur (1.3 cm vs. 6.4 mm). Furthermore, we reduce H. gaoligongense and Pendulorchis gaoligongense var. lushuiensis to the synonymy of H. himalaicum, as there are no discernible morphological differences between them, and they both inhabit the same climate type, namely the subtropical highland climate.